2015
DOI: 10.1038/srep14097
|View full text |Cite|
|
Sign up to set email alerts
|

Surfactant-Templated Synthesis of Polypyrrole Nanocages as Redox Mediators for Efficient Energy Storage

Abstract: Preparation of conducting-polymer hollow nanoparticles with different diameters was accomplished by surfactant templating. An anionic surfactant, namely sodium dodecylbenzenesulfonate, formed vesicles to template with the pyrrole monomer. Subsequent chemical oxidative polymerization of the monomer yielded spherical polypyrrole (PPy) nanoparticles with hollow interiors. The diameter of the hollow nanoparticles was easily controlled by adjusting the concentration of the surfactant. Subsequently, the size-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…In general, nanofiller materials enhance the performance of nanocomposites in various applications [114]. Ann et al [115] reported PPy hollow nanoparticles as the specific capacitance of C sp = 326 Fg −1 , which had two times higher than PPy. Its charge/discharge capacitance retention was obtained to be 86% even following 10.000 cycles.…”
Section: Ruo 2 and Nanofiller-reinforced Conducting Polymersmentioning
confidence: 99%
“…In general, nanofiller materials enhance the performance of nanocomposites in various applications [114]. Ann et al [115] reported PPy hollow nanoparticles as the specific capacitance of C sp = 326 Fg −1 , which had two times higher than PPy. Its charge/discharge capacitance retention was obtained to be 86% even following 10.000 cycles.…”
Section: Ruo 2 and Nanofiller-reinforced Conducting Polymersmentioning
confidence: 99%
“…Note that molecular templating is not only used to control the morphology of the resultant nanoparticles [66], it also affects the doping state of the CPs, which determines the electrical properties [67]. A recent notable example of such a formation mechanism is outlined in Figure 7.…”
Section: Recent Advances In the Synthesis Of Cp Nanomaterialsmentioning
confidence: 99%
“…The fabrication of these hybrids can be commonly achieved via the combination of CPs and inorganic species in the nanometer regime, as discussed above. A notable example is manganese oxide (MnO x )/CP nanohybrids [51,67,111,112]. Because MnO x can act as a reactive template in an acidic medium for the chemical polymerization of CP, direct CP nanocoating has been made on the surface of MnO x .…”
Section: Novel Trends For Synthesis Of Cp Nanohybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of conducting polymers in a variety of applications (including electrochemical capacitors) has been extensively explored 12 13 14 15 16 17 ; this is because of the ease of synthesis and functionalization, reversible redox properties, and flexibility of these materials. In order to further improve their properties, considerable effort has been devoted to tailoring the sizes and morphologies of the nanoscale components of conducting polymers 18 19 20 21 .…”
mentioning
confidence: 99%